Inorganic fiber composite material and preparation method thereof, multilayer material and use thereof

Through the fusion of the inorganic fiber layer and the glass layer and the SiO2 content gradient control, the problems of fragility of glass and heavy ceramic carrier plates are solved, and high-performance inorganic fiber composite materials are prepared, which are suitable for applications such as copper clad plates and photovoltaic cover plates. The material is lightweight, high strength and scratch resistance.

CN118578726BActive Publication Date: 2024-12-27ANHUI ESTONE MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411066978.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-27
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

The glass packaging loading plate is fragile and has poor aging resistance. The ceramic base loading plate is heavy and costly, making it difficult to meet the application needs of copper clad plates.

Method used

The inorganic fiber layer is fused with the glass layer, and an integrated material is formed through melting and hot pressing technology, and the SiO2 content gradient is controlled to improve the binding force, and an inorganic fiber composite material with elastic deformation ability and high thermal stability is prepared.

Benefits of technology

The high Young's modulus, shear modulus and low thermal expansion coefficient of inorganic fiber composite materials are achieved, which reduces weight and enhances scratch resistance. It is suitable for photovoltaics, display screens and scratch-resistant materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118578726B_ABST
    Figure CN118578726B_ABST
Patent Text Reader

Abstract

The present invention discloses an inorganic fiber composite material and a preparation method thereof, a multilayer material and use thereof, and relates to the technical field of inorganic composite materials. The inorganic fiber composite material comprises an inorganic fiber layer and a glass layer, wherein the glass layer is located on at least one side of the inorganic fiber layer or inside the inorganic fiber layer. The present invention solves the problem of glass fragility by fusing the inorganic fiber layer and the glass layer to form an integrated material. The inorganic fiber composite material is prepared by controlling the silicon dioxide content in the inorganic fiber layer and the glass layer to improve the bonding force between the glass layer and the inorganic fiber layer. The inorganic fiber composite material has good elastic deformation ability, thermal stability and high photovoltaic transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic composite materials, and in particular to an inorganic fiber composite material and a preparation method thereof, a multilayer material and uses thereof. Background Art

[0002] Copper clad laminate (CCL) is the most important basic material in PCB manufacturing. It is mainly obtained by cladding copper foil on the package substrate and is responsible for the conductivity, insulation, and support of the PCB. According to the different package substrates, copper clad laminates are mainly divided into resin-based and ceramic-based. The resin-based laminate is mainly obtained by drying epoxy resin + fiber to obtain a semi-cured sheet, and then stacking multiple semi-cured sheets. The ceramic-based laminate is mainly made of inorganic powders such as alumina, aluminum nitride, and silicon carbide, which are obtained by pressing and sintering. It has the advantages of high strength and corrosion resistance. However, the resin-based laminate is not resistant to aging, and there is precipitation of organic components during use, which is easy to corrode the circuit. The ceramic-based laminate is thicker, has a higher specific gravity, and has grain boundaries, which have an impact on the application of copper clad laminates.

[0003] In order to solve these problems, technicians in this field have proposed using glass as a packaging substrate. Although glass can be thinner than a ceramic substrate, the copper-clad laminate needs to be punched. During the punching process, the glass has poor flexibility and is easy to break. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing an inorganic fiber composite material, by fusing an inorganic fiber layer and a glass layer to form an integrated material, thereby solving the problem of glass fragility; and by controlling the silica content in the inorganic fiber layer and the glass layer to improve the bonding force between the glass layer and the inorganic fiber layer, an inorganic fiber composite material with good elastic deformation ability and thermal stability and high photovoltaic transmittance is prepared.

[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0006] One of the objects of the present invention is to provide an inorganic fiber composite material, comprising an inorganic fiber layer and a glass layer, wherein the glass layer is a continuous phase and is located on at least one side of the inorganic fiber layer or inside the inorganic fiber layer.

[0007] The glass layer is integrated with the inorganic fiber layer by melting.

[0008] The SiO2 in the glass layer is uniformly distributed or the SiO2 content changes in a gradient from the inorganic fiber layer to the glass layer.

[0009] The second object of the present invention is to provide a method for preparing the inorganic fiber composite material, wherein the glass powder is prepared into a slurry and then composited with the inorganic fiber fabric by coating or impregnation, and after drying, the glass powder and the inorganic fiber fabric are integrated by hot pressing.

[0010] The third object of the present invention is to provide a method for preparing the inorganic fiber composite material, wherein the inorganic fiber or inorganic fiber fabric is integrated with the glass plate by hot pressing.

[0011] A fourth object of the present invention is to provide a multilayer material obtained by stacking multiple layers of the inorganic fiber composite material and then hot pressing them.

[0012] The fifth object of the present invention is to provide the use of the inorganic fiber composite material or multilayer material as a packaging carrier, photovoltaic cover glass, liquid crystal display packaging backplane, and scratch-resistant material.

[0013] The beneficial effects of the present invention are:

[0014] (1) Compared with the existing glass-based packaging substrate, the inorganic fiber composite material of the present invention has higher Young's modulus and shear modulus, better flexibility, and is not easy to break when punched.

[0015] (2) Compared with the existing photovoltaic cover glass (the thinnest thickness is 1.5 mm), the inorganic fiber composite material of the present invention is thinner (0.042 mm), which can reduce the weight of the photovoltaic module.

[0016] (3) Compared with the existing supporting glass for display screens (such as float glass and ultra-clear glass), the inorganic fiber composite material of the present invention has certain flexibility and high strength, and can be used as a substrate; and because of its thinner thickness, it can reduce the weight of the display screen. It can also be used as a scratch-resistant material, for example, as a plastic substitute for the front desk of a car. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the structure of an inorganic fiber composite material - one side is a glass layer;

[0018] Figure 2 It is a schematic diagram of the structure of the inorganic fiber composite material - both sides are inorganic fiber layers;

[0019] Figure 3 Schematic diagram of the structure of an inorganic fiber composite material - glass layers on both sides. DETAILED DESCRIPTION

[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0021] The invention provides an inorganic fiber composite material, comprising an inorganic fiber layer and a glass layer. The glass layer is a continuous phase and is located on at least one side of the inorganic fiber layer or inside the inorganic fiber layer.

[0022] Furthermore, the glass layer is integrated with the inorganic fiber layer by melting. Figures 1 to 3 As shown, the inorganic fiber composite material can be a glass layer located on one side of the inorganic fiber layer, or an inorganic fiber layer in the middle and glass layers on both sides, or a glass layer in the middle and inorganic fiber layers on both sides. It should be noted that in order to better show different materials in the figure, the inorganic fiber layer and the glass layer have obvious layers, and in fact the inorganic fiber layer can be in the glass layer.

[0023] Furthermore, the inorganic fiber layer is at least one of inorganic fibers or inorganic fiber fabrics.

[0024] Furthermore, the inorganic fiber is selected from at least one of inorganic non-metallic fibers such as alumina fiber, glass fiber, carbon fiber, basalt fiber, etc. Other materials with similar structures to these fibers may also be applicable, such as whiskers with a certain aspect ratio.

[0025] Furthermore, the inorganic fiber fabric is a cloth or mesh made of at least one of inorganic non-metallic fibers such as alumina fiber, glass fiber, carbon fiber, basalt fiber, etc. Since silicon and aluminum-based fibers have good compatibility with glass layers, the inorganic fiber fabric is preferably glass fiber cloth.

[0026] Furthermore, the glass fiber cloth is made of at least one of silicate glass fiber and quartz glass fiber. For example, silicate glass fiber is used to make silicate glass fiber cloth, quartz glass fiber is used to make quartz glass fiber cloth, and silicate / quartz glass fiber cloth is used to make silicate glass fiber and quartz glass fiber.

[0027] Furthermore, the SiO2 content in the glass layer is 30-100wt%.

[0028] Furthermore, SiO2 is uniformly distributed in the glass layer or the SiO2 content changes in a gradient from the inorganic fiber layer to the glass layer.

[0029] In order to reduce the poor compatibility between the glass fiber cloth and the glass layer due to the difference in composition and improve the overall performance of the composite material, the SiO2 content in the glass layer of the inorganic fiber composite material changes gradually from the glass fiber cloth to the glass layer. For example, the SiO2 content in the quartz glass fiber cloth is 100wt%, and the SiO2 content in the glass layer gradually transitions from 100wt% to 30wt%.

[0030] Furthermore, the dielectric constant (1MHz) of the inorganic fiber composite material is 3.7-4.1. The smaller the dielectric constant, the better the quality of the high-speed transmission signal and the faster the rate. The dielectric constant of the commonly used PCB medium FR4 material is 4.2-4.7, so the dielectric properties of the inorganic fiber composite material of the present invention can meet the requirements for use on PCB.

[0031] Furthermore, the thermal expansion coefficient of the inorganic fiber composite material is (0.5~2.5)×10 ~6 / ℃. In the present invention, the glass fiber composite material prepared with quartz glass fiber cloth as the matrix has a low thermal expansion coefficient ((0.5~0.6)×10 ~6 / ℃). The smaller the thermal expansion coefficient, the better the dimensional stability of the material.

[0032] Furthermore, the thickness of the inorganic fiber composite material is 0.04-1 mm, and can be selected from any thickness within the range, such as 0.1 mm, 0.2 mm, 0.3 mm, 0.5 mm, and 0.9 mm.

[0033] The present invention provides a method for preparing the inorganic fiber composite material, wherein glass powder is prepared into slurry and then composited with inorganic fiber fabric by coating or dipping, and after drying, the glass powder and the inorganic fiber fabric are integrated by hot pressing.

[0034] Furthermore, the glass powder is selected from at least one of silicate glass powder and silicon dioxide. The silicate glass powder and silicon dioxide used to prepare the glass layer are both electronic grade.

[0035] Furthermore, the silicon dioxide is selected from at least one of fumed silicon dioxide, precipitated silicon dioxide, porous silicon dioxide, natural quartz powder, fused quartz powder, and silica sol. In order to further improve the photovoltaic transmittance of the inorganic fiber composite material when used as photovoltaic glass, the silicon dioxide includes porous silicon dioxide.

[0036] Furthermore, the coating is one-time coating or multiple coatings.

[0037] Further, the impregnation is one-time impregnation or multiple impregnations. For example, SiO2 powder is coated or impregnated on the surface of the quartz glass fiber cloth for the first time, silicate glass powder with 80wt% SiO2 content is coated or impregnated for the second time, and silicate glass powder with 60wt% SiO2 content is coated or impregnated for the third time.

[0038] The present invention provides another method for preparing an inorganic fiber composite material, wherein inorganic fibers or inorganic fiber fabrics are melted into one with a glass plate by hot pressing.

[0039] The present invention provides a multilayer material, which is obtained by hot pressing the inorganic fiber composite material after multiple layers are stacked. The multilayer inorganic fiber composite material can be hot pressed according to the use requirements to obtain a multilayer material with a greater thickness. The thickness of the multilayer material is 0.1 to 20 mm.

[0040] Furthermore, the hot pressing is selected from at least one of roller pressing, flat plate pressing and isostatic pressing.

[0041] The present invention provides the use of the inorganic fiber composite material or multilayer material as a packaging carrier, photovoltaic cover glass, liquid crystal display packaging backplane, and scratch-resistant material. Since the inorganic fiber composite material of the present invention has outstanding advantages over existing glass in terms of light transmittance, strength, dielectric properties, lightness, and temperature resistance, it can be used as a packaging carrier, photovoltaic cover glass, liquid crystal display packaging backplane, etc. as needed, and can also replace non-scratch-resistant materials such as plastics.

[0042] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available.

[0043] Silicate glass powder: Model EF-3810-3 (D50 = 1.5 μm) and EF-3810-4 (D50 = 1.5 μm), from Changxing Technology Co., Ltd.

[0044] Fused quartz powder: Model SJS-0015 (D50=1.5 μm), from Anhui Yishitong Materials Technology Co., Ltd.

[0045] Porous silica: Model SS-002D, D50 = 2 μm, specific surface area 220 m 2 / g, sourced from Anhui Yishitong Materials Technology Co., Ltd.

[0046] Silicate glass fiber cloth: specification 106, thickness 0.033 mm, sourced from Taiwan Glass Group.

[0047] Quartz glass fiber cloth: Model SJ108, thickness 0.03 mm, sourced from Henan Shenjiu Tianhang New Materials Co., Ltd.

[0048] Carbon fiber cloth: specification 12K, weight 80 g / m 2 , from OXEON AB.

[0049] Alumina fiber cloth: Model 2525-P, thickness 0.12 mm, from NITIVY Co., Ltd.

[0050] Short glass fiber: Model 871, diameter 13 μm, length 32 mm, sourced from Taiwan Glass Group.

[0051] Silicate glass plate: Model Eagle XG, thickness 0.1 mm, sourced from Corning Incorporated.

[0052] Example 1 (silicate glass fiber cloth + silicate glass powder + one-side coating + roller pressing)

[0053] Silicate glass powder EF-3810-3 was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the silicate glass fiber cloth, and the thickness of the glass layer was 10 μm after drying. The glass layer and the glass fiber cloth were integrated under roller pressing at 580°C to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0054] Example 2 (silicate glass fiber cloth + silicate glass powder + one-time double-sided coating + roller pressing)

[0055] Silicate glass powder EF-3810-3 was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on both sides of the silicate glass fiber cloth. After drying, the thickness of the single-sided glass layer was 5 μm. The glass layer and the glass fiber cloth were integrated under roller pressing at 580°C to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0056] Example 3 (silicate glass fiber cloth + silicate glass powder + fused quartz powder + multiple single-sided coating + silica content changes gradually from glass fiber cloth to glass layer + roller pressing)

[0057] The silicate glass powder EF-3810-3 and the fused quartz powder were fully mixed to obtain two mixed powders with SiO2 contents of 50wt% and 80wt%, respectively. The two mixed powders and the fused quartz powder were dispersed in water to prepare three slurries with a solid content of 30%. The three slurries were coated on the surface of the silicate glass fiber cloth in a gradient change of SiO2 content of 50wt%, 80wt% and 100wt%, and the total thickness of the glass layer after drying was 10 μm. The glass layer was integrated with the glass fiber cloth under roller pressing at 580℃ to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0058] Example 4 (quartz glass fiber cloth + silicate glass powder + fused silica powder + multiple single-sided coating + silica content changes from glass fiber cloth to glass layer in a gradient + roller pressing)

[0059] The silicate glass powder EF-3810-3 and the fused quartz powder were fully mixed to obtain two mixed powders with SiO2 contents of 30wt% and 80wt%, respectively. The fused quartz powder and the two mixed powders were dispersed in water to prepare three slurries with a solid content of 30%. The three slurries were coated on the surface of quartz glass fiber cloth in sequence according to a gradient change of SiO2 content of 100wt%, 80wt% and 30wt%. After drying, the total thickness of the glass layer was 13 μm. The glass layer was integrated with the glass fiber cloth under roller pressing at 900℃ to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0060] Example 5 (quartz glass fiber cloth + silicate glass powder + fused silica powder + one-side coating + roller pressing)

[0061] The silicate glass powder EF-3810-3 and the fused quartz powder were fully mixed to obtain a mixed powder with a SiO2 content of 50wt%, and the mixed powder was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the surface of the quartz glass fiber cloth, and the thickness of the glass layer was 13 μm after drying. The glass layer was integrated with the glass fiber cloth under roller pressing at 900℃ to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0062] Example 6 (quartz glass fiber cloth + fused silica powder + one-side coating + roller pressing)

[0063] Fused quartz powder was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the surface of quartz glass fiber cloth, and the thickness of the glass layer was 13 μm after drying. The glass layer and the glass fiber cloth were integrated under roller pressing at 900°C to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0064] Example 7 (silicate glass fiber cloth + silicate glass powder + quartz powder + one-side coating + roller pressing)

[0065] The silicate glass powder EF-3810-3 and the fused quartz powder were fully mixed to obtain a mixed powder with a SiO2 content of 50wt%, and the mixed powder was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the surface of the silicate glass fiber cloth, and the thickness of the glass layer was 10 μm after drying. The glass layer was integrated with the glass fiber cloth under roller pressing at 580℃ to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0066] Example 8 (silicate glass fiber cloth + silicate glass powder + porous silica + one-side coating + roller pressing)

[0067] Silicate glass powder EF-3810-3 and porous silica were mixed in a mass ratio of 98:2 and dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the surface of silicate glass fiber cloth, and the thickness of the glass layer was 10 μm after drying. The glass layer was integrated with the glass fiber cloth under roller pressing at 580°C to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0068] Example 9 (silicate glass fiber cloth + silicate glass powder + porous silica + one-side coating + isostatic pressing)

[0069] Silicate glass powder EF-3810-3 and porous silica were mixed in a mass ratio of 98:2 and dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the surface of the silicate glass fiber cloth, and the thickness of the glass layer was 10 μm after drying. The slurry was placed in a hot press and isostatically pressed at 580°C (50 MPa / 5 min) to fuse the glass layer with the glass fiber cloth to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0070] Example 10 (silicate glass fiber cloth + silicate glass powder + one-time impregnation + roller pressing)

[0071] Silicate glass powder EF-3810-3 was dispersed in water to prepare a slurry with a solid content of 30%. Silicate glass fiber cloth was immersed in the slurry, and the thickness after drying was 0.043 mm. The glass layer and the glass fiber cloth were integrated by roller pressing at 580°C to obtain a glass fiber composite material with a thickness of 0.042 mm.

[0072] Example 11 (Silicate glass fiber cloth + glass plate + isostatic pressing)

[0073] The silicate glass plate and the silicate glass fiber cloth were stacked and placed in a hot press, heated to 580°C and isostatically pressed (50 MPa / 5 min) to obtain a glass fiber composite material with a thickness of 0.1 mm.

[0074] Example 12 (carbon fiber cloth + silicate glass powder + one-side coating + roller pressing)

[0075] Silicate glass powder EF-3810-3 was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the carbon fiber cloth. After drying, the thickness of the glass layer was 10 μm. The glass layer and the carbon fiber cloth were integrated under roller pressing at 580°C to obtain a carbon fiber composite material with a thickness of 0.72 mm.

[0076] Example 13 (alumina fiber cloth + silicate glass powder + one-side coating + roller pressing)

[0077] Silicate glass powder EF-3810-3 was dispersed in water to prepare a slurry with a solid content of 30%. The slurry was coated on one side of the alumina fiber cloth. After drying, the glass layer had a thickness of 10 μm. The glass layer was integrated with the alumina fiber cloth under roller pressing at 580 °C to obtain an alumina fiber composite material with a thickness of 0.12 mm.

[0078] Example 14 (two layers of silicate glass fiber cloth sandwiched with glass plate + isostatic pressing)

[0079] The silicate glass plate was sandwiched between two layers of silicate glass fiber cloth, and the plate was placed in an isostatic press and heated to 580°C for isostatic pressing (50 MPa / 5 min) to obtain a glass fiber composite material with a thickness of 0.1 mm.

[0080] Example 15 (two layers of glass sandwiched with short glass fibers + isostatic pressing)

[0081] Two layers of silicate glass are used to sandwich the short glass fibers, and the amount of short glass fibers is 10 g / dm 2 , placed in an isostatic press and heated to 580°C for isostatic pressing (50 MPa / 5 min) to obtain a glass fiber composite material with a thickness of 0.2 mm.

[0082] The performance of the inorganic fiber composite materials prepared in Examples 1 to 15 was tested, and the results are shown in Table 1.

[0083] The test of Young's modulus and shear modulus is in accordance with GB / T 7962.6-2010;

[0084] The test of thermal expansion coefficient is in accordance with GB / T 7962.16-2010;

[0085] The dielectric constant is tested in accordance with GB / T 31838.6-2021.

[0086] Table 1

[0087]

[0088] From Table 1 we can see that:

[0089] It can be seen from Examples 1 and 2 that, compared with single-sided coating, preparing a glass layer on a glass fiber cloth by double-sided coating can make the glass fiber composite material have a higher Young's modulus and shear modulus, but the thermal expansion coefficient does not change much.

[0090] It can be seen from Examples 3 and 4 that multiple coatings of glass fiber cloth with slurries having different SiO2 contents can further improve the elastic deformation capacity of the material. The reason may be that there is a difference between the SiO2 content in the silicate and the SiO2 content in the glass layer. The SiO2 content in the glass fiber composite material changes in a gradient from the glass fiber cloth to the glass layer, thereby reducing the gradient difference, which is beneficial to enhancing the bonding force between the glass fiber cloth and the glass layer, thereby improving the elastic deformation capacity of the material.

[0091] It can be seen from Examples 1 and 7, 5 and 6 that, compared with preparing a glass layer using silicate glass powder on silicate glass fiber cloth and preparing a glass layer using quartz powder on quartz glass fiber cloth, preparing a glass layer using a mixed powder of silicate glass powder and quartz powder on silicate glass fiber cloth and quartz glass fiber cloth can improve the Young's modulus and shear modulus of the glass fiber composite material.

[0092] It can be seen from Examples 4-6 that, compared with silicate glass fiber cloth, by preparing a glass layer on quartz glass fiber cloth, the obtained glass fiber composite material has a lower thermal expansion coefficient and good thermal stability.

[0093] It can be seen from Example 8 and Example 9 that, compared with hot isostatic pressing, hot rolling can make the glass fiber cloth and the glass layer have a stronger bonding force.

[0094] It can be seen from Examples 12 and 13 that although carbon fiber and alumina fiber are not silicon-based materials, they can achieve a reinforcing effect. The dielectric constant of the carbon fiber composite material prepared in Example 12 is relatively small. The possible reason is that the carbon fiber interface reacts with the silicon dioxide in the glass layer to achieve a better combination, but the price of carbon fiber is relatively high; compared with quartz glass fiber cloth, silicate glass fiber cloth, and carbon fiber, the dielectric constant of alumina fiber is the largest, and the attenuation rate of the transmission signal increases.

[0095] The performance of the glass fiber composite materials prepared in Examples 1 to 11, 14 and 15 as ultra-clear patterned glass for photovoltaic use was tested in accordance with GB / T 30984.1-2015. The results are shown in Table 2.

[0096] Table 2

[0097]

[0098] From Table 2 we can see that:

[0099] The glass fiber composite materials prepared in Examples 1 to 11, 14, and 15 can meet the requirements of GB / T 30984.1-2015, and compared with the existing ultra-white embossed glass for photovoltaics, they are thinner in thickness and can reduce the weight of photovoltaic modules.

[0100] It can be seen from Examples 1 and 8 that adding a small amount of porous silica during the preparation of the glass layer can improve the photovoltaic transmittance of the glass fiber composite material. The possible reason is that the porous silica can prevent sedimentation and improve the uniformity of the glass layer.

[0101] Application examples 1~11, 14

[0102] Twelve layers of the glass fiber composite material obtained in Examples 1 to 11 and 14 were stacked and isostatically pressed (80 MPa / 5 min) at 580° C. (Examples 1, 2, 3, 4, 7, 8, 9, 10, 11, 14) or 900° C. (Examples 5 and 6) to obtain a carrier plate with a thickness of 0.5 mm.

[0103] Application Example 15

[0104] Three layers of the glass fiber composite material obtained in Example 15 were stacked and isostatically pressed at 580° C. (80 MPa / 10 min) to obtain a carrier plate with a thickness of 0.6 mm.

[0105] Comparative Example 1

[0106] CCL glass carrier 0.5 mm (Corning® Gorilla® Glass Victus® 2).

[0107] The performance tests were carried out on the carriers made from Examples 1 to 11, 14, and 15 and the glass carrier in Comparative Example 1. The results are shown in Table 3.

[0108] The test of Young's modulus and shear modulus is in accordance with GB / T 7962.6-2010;

[0109] The test of thermal expansion coefficient is in accordance with GB / T 7962.16-2010;

[0110] The dielectric constant is tested in accordance with GB / T 31838.6-2021.

[0111] Table 3

[0112]

[0113] From Table 3 we can see that:

[0114] The dielectric constant of the substrates made in application examples 1 to 11, 14, and 15 is close to that of a glass substrate, and lower than the dielectric constant of the commonly used PCB medium FR4 material, which is 4.2 to 4.7, and can be used as a packaging substrate.

[0115] The Young's modulus and shear strength of the carrier plates made in Application Examples 1 to 11, 14, and 15 are higher than those in Comparative Example 1. The reason may be that the glass fiber cloth has higher strength in the warp and weft directions, and can improve the elastic deformation capacity of the material after being compounded with the glass layer; and the thermal expansion coefficient of the carrier plates made in Application Examples 1 to 11, 14, and 15 is lower than that in Comparative Example 1, indicating that they have good thermal stability.

[0116] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An inorganic fiber composite material, characterized in that: It comprises an inorganic fiber layer and a glass layer, wherein the glass layer is a continuous phase and is located on at least one side of the inorganic fiber layer; The glass layer is integrated with the inorganic fiber layer by melting; The SiO2 content in the glass layer changes in a gradient from the inorganic fiber layer to the glass layer; The preparation method of the inorganic fiber composite material is as follows: fully mixing silicate glass powder and fused quartz powder to obtain mixed powders with different SiO2 contents, dispersing the fused quartz powder and the mixed powder in water to prepare slurry; coating the slurry on the surface of silicate glass fiber cloth or quartz glass fiber cloth in sequence according to the gradient change of SiO2 content, drying, and rolling at 580°C or 900°C to fuse the glass layer with the glass fiber cloth.

2. The inorganic fiber composite material according to claim 1, characterized in that: The SiO2 content in the glass layer is 30-100wt%.

3. The inorganic fiber composite material according to claim 1, characterized in that: The dielectric constant of the inorganic fiber composite material is 3.7-4.1; the thermal expansion coefficient is (0.5-2.5)×10 ~6 / ℃.

4. The inorganic fiber composite material according to claim 1, characterized in that: The thickness of the inorganic fiber composite material is 0.04-1 mm.

5. A multilayer material, characterized in that: The multilayer material is obtained by stacking multiple layers of the inorganic fiber composite material according to any one of claims 1 to 4 and then hot pressing them.

6. The multilayer material according to claim 5, characterized in that: The thickness of the multilayer material is 0.1-20 mm.

7. Use of the inorganic fiber composite material according to any one of claims 1 to 4 or the multilayer material according to claim 6 as a packaging carrier, photovoltaic cover glass, liquid crystal display packaging backplane, or scratch-resistant material.